Aspectos neurológicos da moléstia de chagas Neurological aspects of Chagas disease - Fritz Köberle (Arquivos de Neuro-Psiquiatria)
Carlos Chagas related in more than two 200 cases, what he called "nervous forms" of trypanosomiasis, that is neurological manifestations from central origin (idiotism, infantilism, pseudo-bulbar paralysis, aphasia, cerebellar ataxia, atetosis, espostic or paralytic diplegia, disbasia). At that time Chagas expressed his concepts as follows: "In relation to the frequency of trypanosomiasis nervous forms we have performed many observations which allow us to state that this disease is the one which causes the largest number of organic affections of the central nervous system, in human pathology". We are plenty convinced by Chagas's statement. By experiments on animals of laboratory we have very often noticed a rather varied neurological symptomatology, being worth point out identical syndromes to those observed by Chagas. Our autopsy material non-rarely include chronic Chagas cases presenting a most varied symtomatology. Among them we have named only three cases of discerebral nanism, a rather rare affection in other parts of the world and relatively frequent in our material. The fact which we have demonstrated, i.e., a relatively great decreasing of number of nervous cells in the peripheral system could happen in the central nervous system as well. Provided that there are only two quantitative works on neuron number diminishing in the central nervous system in mice and rats we decline to go into further details about central neuropathies in man. We emphasized the necessity to perform researches on this field by means of intimate collaboration between clinicians and pathologists, as the only way to confirm on scientific basis all that was observed by the panoramic and genial vision of Carlos Chagas.